Injection molding of polymeric micro-mixer - Loh, Eric Chee Soon. (2010)
Injection Molding is an important process used in the manufacture of microfluidic devices. In this project, two polymers – polymethyl metacrylate (PMMA) and Cyclic olefin copolymer (COC) are studied to understand the effects of molding parameters and to achieve industrial standard quality yield.